IMPLEMENTASI KEBIJAKAN RETRIBUSI PELAYANAN DAN PENATAAN PARKIR DI TEPI JALAN UMUM KOTA SEMARANG - Aprilianto, Arista; Suwitri, Sri (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Semarang is one of biggest city in Java Island, so have potential of substantial revenue, including charges for services from the public’s roadside parking. With the implementation and surveillance of parking service fees in the edge of public road at Semarang City aimed to explore the potential of the area by maximizing revenue as source of income to improve services for good regional development. One of the potential income derived from the retribution for public roadside parking service considering the number of vehicles in Semarang annually increased. For example the number of 2-wheel vehicles in 2010 about 119019 units and increased to 151286 in 2013. However the implementation are far from the current target because many found numerous violations. This study aims to describe how the implementation and surveillance of parking service fees in the edge of public road at Semarang and to investigate the inhibiting aspects of policy implementation. The method used is descriptive qualitative theory from Mazmanian and Sabatier also Van Meter and Horn. The results of the study in the location shows that the inhibiting aspects of policy implementation that is the attitude and communication. Based on the problems that found in the study, the authors giving out recommendations for improvements to existing problems such as: socialization and periodic supervision, increasing resolute sanctions and increasing the effectiveness of coordination between the implementing agencies.